Correlation Between Time Management, Compensation, and Performance: A Case Study of Nania Health Center - Felix Chandra; Nurul Maghfirah (International Journal of Management Research and Economics, 2025)
This study aims to examine the impact of time management and compensation on employee performance at Nania Health Center. An explanatory approach with quantitative design is used to identify and explain the causal relationship between the variables studied. The research sample consisted of the entire employee population of 39 people, selected through saturated sampling techniques. Data were collected using a questionnaire and analyzed through validity tests, reliability tests, and classical assumption tests, with the influence of variables tested using multiple regression. The results of the analysis indicate that time management has a positive and significant effect on employee performance, as well as that compensation is proven to have a significant positive effect on performance.